Desempenho ortográfico de escolares de 2o ao 5o ano do ensino privado do município de Londrina - Batista, Andrea Oliveira [UNESP]; Capellini, Simone Aparecida [UNESP] (My University, 2011)
To elaborate a battery of tests that aimed to determine the level of orthographic knowledge of the alphabetic writing system of Brazilian Portuguese, to characterize, to compare and to classify the performance of students from 2nd to 5th grades of private education according to the semiology of errors. Methods: We developed specific tests for this purpose, following the spelling principles of Portuguese in Brazil. We evaluated 120 children from the 2nd to 5th grades, 30 students of each level divided into four groups, respectively, GI, GII, GIII and GIV. The tests elaborated and applied were divided into: collective version (written in letters of the alphabet, randomized dictation of letters, word dictation, nonword dictation, dictation with pictures, thematic writing induced by picture) and individual version (dictation of sentences, purposeful error, spelled dictation, spelling lexical memory). Results: There was a statistically significant difference in inter-group comparison indicating that there was an increase in average accuracy for all tests of the individual and collective version. With the increase of grade level, the groups decreased the average of writing errors based on the semiology of the error. Conclusion: Our data indicate that the profile of spelling acquisition of the Portuguese writing system found in these private students may be indicative of normal development of children's writing in this population.

Elaborar uma bateria de provas que visam a avaliar o nível de conhecimento ortográfico do sistema de escrita alfabético do português do Brasil; caracterizar, comparar e classificar o desempenho dos escolares de 2º ao 5º ano do ensino particular segundo a semiologia dos erros. Método: Foram elaboradas provas específicas para esse fim, seguindo os princípios ortográficos da língua portuguesa do Brasil. Foram avaliados 120 escolares do 2º ao 5º ano, sendo 30 de cada série escolar divididos em quatro grupos, respectivamente GI, GII, GIII e GIV. As provas elaboradas e aplicadas foram divididas em: versão coletiva (escrita das letras do alfabeto, ditado aleatório das letras do alfabeto, ditado de palavras, ditado de pseudopalavras, ditado com figuras, escrita temática induzida por figura) e versão individual (ditado de frases, erro proposital, ditado soletrado, memória lexical ortográfica). Resultados: Houve diferença estatisticamente significante na comparação intergrupos, indicando o aumento da média de acertos em todas as provas da versão coletiva e individual. Com o aumento da seriação escolar, os grupos diminuíram a média de erros na escrita com base na semiologia do erro. Conclusão: Os dados deste estudo indicam que o perfil da aquisição da ortografia do sistema de escrita do português encontrado nesses escolares do ensino privado pode ser indicativo do funcionamento normal de desenvolvimento da escrita infantil nessa população.
Spelling performance of students of 2nd to 5th grade from private education in the city of Londrina
Keywords: Avaliação; Ortografia; escrita manual; Escolaridade